Is autophagy associated with diabetes mellitus and its complications? - Bhattacharya, Debalina; Mukhopadhyay, Mainak; Bhattacharyya, Maitree; Karmakar, Parimal (Technische Universität Dortmund, 2018)
Diabetes mellitus (DM) is an endocrine disorder. In coming decades it will be one of the leading causes of death globally. The key factors in the pathogenesis of diabetes are cellular injuries and disorders of energy metabolism leading to severe diabetic complications. Recent studies have confirmed that autophagy plays a pivotal role in diabetes and its complications. It has been observed that autophagy regulates the normal function of pancreatic β cells and insulin-target tissues, such as skeletal muscle, liver, and adipose tissue. This review will summarize the regulation of autophagy in diabetes and its complications, and explore how this process would emerge as a potential therapeutic target for diabetes treatment.
A review
EXCLI Journal;Vol. 17 2018
Keywords: Type 2 diabetes mellitus; T2DM; Autophagy; Retinopathy; Cardiomyopathy; Nephropathy; 610